Visiting Langston - Perdomo, Willie; Collier, Bryan (New York : Henry Holt and Co., 2002)
A poem to celebrate the African American poet, Langston Hughes, born on February 1, 1902.
Keywords: Hughes, Langston, -- 1902-1967 -- Juvenile poetry; Hughes, Langston, -- 1902-1967 -- Poetry; African American poets -- Juvenile poetry; Children's poetry, American; Poets -- Juvenile poetry; African Americans -- Poetry; American poetry